Early operative comparison of two epicardial left atrial appendage occluding systems applied during off-pump coronary revascularisation in patients with persistent atrial fibrillation - Suwalski, Grzegorz; Emery, Robert; Gryszko, Leszek; Kaczejko, Kamil; Żegadło, Arkadiusz; Frankowska, Emilia; Mróz, Jakub; Skrobowski, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Introduction: Atrial fibrillation (AF) increases long-term mortality and stroke rate in patients having coronary artery bypass grafting (CABG). Because oral anticoagulation (OAC) is associated with both a significant incidence of discontinuation and well known complication rates, left atrial appendage occlusion might be beneficial for stroke prevention. This study presents the first clinical and practical comparison of two epicardial left appendage occluders (LAAO) accruing experience in application during off-pump coronary revascularisation in patients with persistent AF. Material and methods: Fifteen consecutive patients with persistent AF were assigned to intraoperative LAA occlusion with either TigerPaw System II (n = 8) or AtriClip (n = 7) device during off-pump CABG and concomitant left atrial epicardial ablation. Both systems were analysed in terms of ease and safety of application along with intraoperative LAA occlusion success. Results: Surgical risk was increased in the study population (mean EuroScore II: 3.2 ± 0.3%). In all patients in the AtriClip group successful off-pump LAA occlusion confirmed by intraoperative transoesophageal echocardiography was achieved. The TigerPaw application was quicker and easier, but in 2 patients it was unsuccessful. During the hospital stay there were no bleeding or thromboembolic events recorded. Conclusions: In a pilot cohort epicardial LAAO during off-pump CABG in patients with persistent AF was performed safely and successfully with an AtriClip device. The TigerPaw System requires technological improvement. It might be useful to adapt the use of the type of occluding device to the LAA morphologic type and target revascularisation vessels to avoid the additional use of a heart posi-tioner or obviate coronary compression.